The Role of Investigators in Handling Child Promiscuity Crimes - Situmorang, Jhon EJ (Faculty of Law, Universitas Lampung, 2023)
This article examined the role of investigators at the Lampung Regional Police in addressing criminal cases of child promiscuity and identified the factors that hindered their effectiveness. This normative juridical research focused on cases handled by the PPA (Protection of Women and Children Unit) investigators of Polda Lampung in 2021, exploring how they managed these sensitive cases. The research was grounded in the frameworks provided by Law Number 8 of 1981 concerning the Criminal Procedure Code and the Police Law, which established the basis for criminal responsibility. The findings revealed that the effectiveness of investigators was significantly constrained by a shortage of personnel and inadequate infrastructure, impacting their ability to manage cases of child promiscuity effectively.